1996
DOI: 10.1164/ajrccm.154.5.8912753
|View full text |Cite
|
Sign up to set email alerts
|

Value of perfusion lung scan in the diagnosis of pulmonary embolism: results of the Prospective Investigative Study of Acute Pulmonary Embolism Diagnosis (PISA-PED).

Abstract: To assess the value of perfusion lung scan in the diagnosis of pulmonary embolism, we prospectively evaluated 890 consecutive patients with suspected pulmonary embolism. Prior to lung scanning, each patient was assigned a clinical probability of pulmonary embolism (very likely, possible, unlikely). Perfusion scans were independently classified as follows: (1) normal, (2) near-normal, (3) abnormal compatible with pulmonary embolism (PE+: single or multiple wedge-shaped perfusion defects), or (4) abnormal not co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
241
1
13

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(261 citation statements)
references
References 20 publications
6
241
1
13
Order By: Relevance
“…For definitive diagnosis, clinical evaluation should be considered together with an objective method (9,10). Currently, the Wells, Geneva, Modified Geneva and Miniati scoring systems formulated based on risk factors and clinical findings have been used in the diagnosis of PTE (7,(11)(12)(13). When the findings were scored and the threshold of the Wells scoring system with numerical limits was defined, higher sensitivity and lower negativity rates were reported.…”
Section: Discussionmentioning
confidence: 99%
“…For definitive diagnosis, clinical evaluation should be considered together with an objective method (9,10). Currently, the Wells, Geneva, Modified Geneva and Miniati scoring systems formulated based on risk factors and clinical findings have been used in the diagnosis of PTE (7,(11)(12)(13). When the findings were scored and the threshold of the Wells scoring system with numerical limits was defined, higher sensitivity and lower negativity rates were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous probabilistic interpretation criteria and the associated reporting methods, according to PIOPED or modified PIOPED, are unsatisfactory [3]. Using PISAPED criteria with clear answers, taking into account vascular anatomy of the lung has clearly improved diagnosis [4]. Efficient lung scintigraphic methods routinely incorporate ventilation studies.…”
Section: Historical Evolution Of Lung Scintigraphymentioning
confidence: 99%
“…(20)(21)26) Criteria for excluding a diagnosis of PTE include normal or quasi-normal perfusion scan, normal pulmonary arteriogram (despite a 3% rate of false-negative results and interobserver discrepancy for subsegmental emboli), inconclusive V/Q mapping results accompanied by negative DVT studies, negative multidetector-row CTA (to be confirmed); and normal levels of the D-dimers associated with low clinical probability. (20)(21)(26)(27)(28) Developing pretest suspicion based on an accurate clinical evaluation is an essential stage in the diagnostic process, facilitating the posttest definition and resulting in a better cost-effectiveness ratio. However, as evidence of the difficulties of developing a solid suspicion, various quite well-delineated prospective studies have demonstrated that objective confirmation of PTE is below 40% among suspected cases, (27)(28)(29) and that approximately 70% of PTE cases diagnosed during autopsies were not previously suspected by the attending physicians.…”
Section: Pte Diagnosismentioning
confidence: 99%
“…(20)(21)(26)(27)(28) Developing pretest suspicion based on an accurate clinical evaluation is an essential stage in the diagnostic process, facilitating the posttest definition and resulting in a better cost-effectiveness ratio. However, as evidence of the difficulties of developing a solid suspicion, various quite well-delineated prospective studies have demonstrated that objective confirmation of PTE is below 40% among suspected cases, (27)(28)(29) and that approximately 70% of PTE cases diagnosed during autopsies were not previously suspected by the attending physicians. (30) …”
Section: Pte Diagnosismentioning
confidence: 99%